Spatial symmetry and contrasting controls of surface pH and aragonite saturation state in the western North Pacific - Li, Cheng-long; Wu, Yingxu; Chen, Kui; Lin, Hongmei; Chen, Liqi; Qi, Di (Frontiers in Marine Science, 2023)
Oceanic uptake of anthropogenic CO2 causes a decrease in seawater pH and aragonite saturation state (Ωarag), a process known as ocean acidification (OA). The western North Pacific is a hotspot for anthropogenic CO2 sinks; however, the spatiotemporal variability of pH and Ωarag and their controlling mechanisms remain unexplored. In this study, we provide high-frequency and high-precision underway measurements of sea surface pCO2 and pH to investigate the distribution and drivers of OA metrics across different hydrochemical gradients in the western North Pacific in late spring 2018, a season with the highest primary production in the year. Our results show that the surface pH reached near air-sea equilibrium in the subtropical zone but gradually increased northward across the Kuroshio Recirculation (KR) zone and peaked in the Kuroshio Extension (KE) zone. We found that sea surface temperature played the most prominent role in regulating pH, which was also counteracted by the effects of air–sea gas exchange and vertical mixing. In contrast, the distribution of Ωarag largely mirrored the pH and was governed by air–sea gas exchange and vertical mixing, the effects of which on Ωarag were enhanced by temperature. Biological activity thrived in the KE zone to increase both pH and Ωarag, which further reinforced the latitudinal pattern of pH, but weakened that of Ωarag. These findings are based on direct in situ measurements of pH and improve our understanding of the spatiotemporal variability of OA metrics in the western North Pacific region.